Nutritional Composition, Polyphenol Content, and Antioxidant Activity of Swiss Chard (Beta vulgaris L. subsp. cicla) - Natália Čeryová; Lidiková, Judita; Grygorieva, Olga; Brindza, Jan; Demianová, Alžbeta; Jurčaga, Lukáš; Harangozo, Ľuboš (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2025)
Swiss chard (Beta vulgaris L. subsp. cicla) is a nutritionally rich leafy vegetable valued for its high bioactive compounds and essential mineral content. This study aimed to evaluate the total polyphenol content (TPC), antioxidant activity (AA), macro- and microelement concentrations, and the presence of selected risk elements (lead and cadmium) in different plant parts (leaves and stems) of two Swiss chard samples. The results revealed that leaves consistently exhibited higher levels of TPC and AA than stems, with values reaching up to 9634 mg GAE.kg-1 DM and 15.9 mmol TE.kg-1 DM, respectively. Mineral analysis confirmed Swiss chard as a good calcium, magnesium, potassium, and iron source, with significant variation between leaves and stems. While leaves were richer in calcium, magnesium, iron, manganese, and zinc, stems contained higher levels of sodium and potassium. Trace element analysis indicated the presence of lead and cadmium in all samples, with lead exceeding the permissible limit in the leaves of one sample. The findings emphasize both the nutritional potential of Swiss chard and the need for environmental monitoring to ensure food safety. The observed variability in chemical composition highlights the influence of plant part, genotype, and environmental conditions. Overall, Swiss chard represents a promising functional food, particularly when cultivated under controlled agroecological practices that minimize contaminant exposure.